Steric Control in Activator‐Induced Nucleophilic Quencher Detachment‐Based Probes: High‐Contrast Imaging of Aldehyde Dehydrogenase 1A1 in Cancer Stem Cells. Issue 3 (31st January 2023) - Oe, Masahiro; Suzuki, Kanae; Miki, Koji; Mu, Huiying; Ohe, Kouichi
Abstract : The cover feature image shows a depiction of cancer stem cell detection using turn‐on fluorescence probe. The quenched probe selectively responds to aldehyde dehydrogenase 1A1 (ALDH1A1) overexpressed in cancer stem cells to emit deep red fluorescence, enabling their high‐contrast live imaging. More information can be found in the Research Article by K. Miki, K. Ohe, and co‐workers .